Recent Insights on the Medicinal Chemistry of Sickle Cell Disease - Santos, Jean Leandro dos [UNESP]; Chin, Chung Man [UNESP] (Bentham Science Publ Ltd, 2011)
Sickle Cell Disease (SCD) is one of the most prevalent hematological diseases in the world. SCD is a genetic disease characterized by punctual mutation that basis on the exchange of glutamic acid to valine in a beta chain of hemoglobin. In deoxygenated state, the interaction among the beta chains leads to hemoglobin polymerization carrying out to deformation of cytoskeleton structure of red blood cells to a sickle shape. Currently, the treatment is performed with the antineoplasic drug hydroxyurea. This review summarizes current knowledge about possible targets and the approaches to discover new compounds to treat the SCD symptoms. Drug design based on therapeutical application and molecular modifications strategies will be discussed.
Keywords: Chelating agents; drug discovery; erythrocyte dehydratation; fetal hemoglobin; hydroxyurea; nitric oxide; sickle cell disease; vasodilatation; hemoglobin modifiers; hemoglobin inducers; gardos channel; sickle cell treatment; vasodilation; phytomedicines